2011
DOI: 10.1111/j.1476-5829.2011.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

DCEMRI: a review and applications in veterinary oncology

Abstract: Dynamic contrast enhanced magnetic resonance imaging (DCE‐MRI) is a functional imaging technique that assesses the physiology of tumour tissue by exploiting abnormal tumour microvasculature. Advances made through DCE‐MRI include improvement in the diagnosis of cancer, optimization of treatment choices, assessment of treatment efficacy and non‐invasive identification of prognostic information. DCE‐MRI enables quantitative assessment of tissue vessel density, integrity, and permeability, and this information can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
(140 reference statements)
0
16
0
Order By: Relevance
“…Dynamic contrast‐enhanced MRI (DCE‐MRI) has the advantage of quantitatively assessing the microcirculation perfusion status of tissues . Semiquantitative description of liver perfusion, such as hepatic portal index (HPoI), and more sophisticated descriptions of tissue vascular properties such as K trans (forward volume transfer constant), V e (extravascular extracellular volume fraction), and V p (plasma volume fraction) can be calculated using the appealing model‐based approaches, ie, classic Tofts model, extended Tofts model, or exchange model .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic contrast‐enhanced MRI (DCE‐MRI) has the advantage of quantitatively assessing the microcirculation perfusion status of tissues . Semiquantitative description of liver perfusion, such as hepatic portal index (HPoI), and more sophisticated descriptions of tissue vascular properties such as K trans (forward volume transfer constant), V e (extravascular extracellular volume fraction), and V p (plasma volume fraction) can be calculated using the appealing model‐based approaches, ie, classic Tofts model, extended Tofts model, or exchange model .…”
mentioning
confidence: 99%
“…13,14 Dynamic contrast-enhanced MRI (DCE-MRI) has the advantage of quantitatively assessing the microcirculation perfusion status of tissues. 15,16 Semiquantitative description of liver perfusion, such as hepatic portal index (HPoI), and more sophisticated descriptions of tissue vascular properties such as K trans (forward volume transfer constant), V e (extravascular extracellular volume fraction), and V p (plasma volume fraction) can be calculated using the appealing modelbased approaches, ie, classic Tofts model, extended Tofts model, or exchange model. 17 Previous DCE-MRI studies have shown that multiple semiquantitative perfusion parameters including arterial blood flow, arterial fraction, and mean transit time could be used to diagnose advanced liver fibrosis and evaluate the severity of liver fibrosis in chronic hepatitis patients.…”
mentioning
confidence: 99%
“…Dynamic contrast-enhanced MRI (DCE-MRI) has recently been investigated in animals. It can be used for assessment of tumor perfusion in soft tissue sarcomas and brain tumors, and to follow tumor responses after hyperthermia and radiation therapy in animals (126).…”
Section: What's On the Horizon For Oncologic Imaging?mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) appears to be better than ultrasound at detecting enlarged abdominal lymph nodes in dogs diagnosed with anal sac adenocarcinoma (Anderson et al, 2013). Dynamic contrast-enhanced MRI is a new tool that is currently being explored to detect tumor perfusion in soft tissue sarcomas and brain tumors and to follow responses after hyperthermia and radiation therapy in animals (Boss et al, 2013). Each of these more sophisticated imaging modalities has the potential to improve patient care.…”
mentioning
confidence: 99%